1981
DOI: 10.1016/0165-1161(81)90022-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequency of sister-chromatid exchanges in alcoholics

Abstract: The frequency of SCES was significantly increased in the alcoholics analyzed (10.6 &/- SD 0.66) when compared to the frequency of a control group (8.4 &/- SD 0.51). Statistical analysis of the data obtained showed that the increase was not apparently related to age, sex, cigarette smoking, duration in years of alcohol abuse, nutritional status or type of alcoholic beverage commonly consumed by the individual. Alcoholics recovering for at least one year from alcohol abuse were examined and the frequency of SCES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1
3

Year Published

1981
1981
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(11 citation statements)
references
References 16 publications
2
5
1
3
Order By: Relevance
“…Alcoholics have been found to have a higher frequency of SCEs, CAs, and MN in their lymphocytes than non-alcoholics [33][34][35], which is in line with the results of our study, with some slight differences. The MN observed in the peripheral blood lymphocytes reflect a complex exposure environment, including bone marrow, blood stream, cell cultures, or mutagen challenge in vitro.…”
Section: Discussionsupporting
confidence: 83%
“…Alcoholics have been found to have a higher frequency of SCEs, CAs, and MN in their lymphocytes than non-alcoholics [33][34][35], which is in line with the results of our study, with some slight differences. The MN observed in the peripheral blood lymphocytes reflect a complex exposure environment, including bone marrow, blood stream, cell cultures, or mutagen challenge in vitro.…”
Section: Discussionsupporting
confidence: 83%
“…The observed increase in level of SCE amongst older subjects could be either due to the presence of cumulative damage caused by long-term exposure to unidentified carcinogens and/or mutagens, or from other factors related to cellular aging such as the relative integrity of the DNA repair process. In addition, an increased SCE frequency has reported in chronic alcoholics (Butler et al 1981), and alcohol consumption has been reported to generate reactive oxygen species presumably through the effect of cytochrome P450 2E1 (Bailey and Cunningham 1998;Mali et al 2001). However, the effect of alcohol on SCE frequency was not observed in our study.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies indicate that gender, age, smoking, and alcohol consumption are among the major confounding factors affecting SCE frequencies [Husgafvel-Pursiainen et al, 1980;Butler et al, 1981;Bonassi et al, 1995;Bolognesi et al, 1997]. To minimize the effects of these potential confounders, all the volunteer patients were nonsmokers and nondrinkers.…”
Section: Resultsmentioning
confidence: 99%